Massacre in Norway: The 2011 Terror Attacks on Oslo and the Utøya Youth Camp - Bromark, Stian (Potomac Books Inc., 2014)
On July 22, 2011, a bomb went off outside government buildings in Oslo, Norway, killing eight people and injuring more than two hundred. Less than two hours later, a gunman claimed sixty-nine lives in a shooting spree at a summer camp on the island of Ut?ya, while terrified and desperate youths tried to hide or swim to the mainland to escape. Massacre in Norway is the first detailed, hour-by-hour account of the two sequential terrorist attacks by lone-wolf terrorist Anders Behring Breivik. To inform his literary reportage, Stian Bromark compiled interviews with survivors, police officers, government employees, boatmen rescuers, and others who experienced the attacksùthe deadliest in Norway since World War II. Massacre in Norway provides crucial, in-depth context for the story including a riveting background portrait of Breivik, the right-wing extremist the police arrested, charged, and convicted of the crime, as well as a history of the Labor Party youth camp on Ut?ya and its significance in the countryÆs political landscape. An epilogue covers the trial in 2012 and interviews with the survivors. Massacre in Norway delivers an insightful portrayal of the darkest day in modern Norwegian history.